2017
DOI: 10.1016/j.fsi.2017.05.039
|View full text |Cite
|
Sign up to set email alerts
|

Suppression of PmRab11 inhibits YHV infection in Penaeus monodon

Abstract: Yellow head virus (YHV) is one of the most serious pathogens that causes worldwide shrimp production loss. It enters the cells via clathrin-mediated endocytosis and utilizes small GTPase Rab proteins such as PmRab5 and PmRab7 for intracellular trafficking. In this study, molecular cloning and functional analysis of Rab11 during YHV infection were investigated. PmRab11 cDNA was cloned by Rapid amplification of cDNA ends (RACEs). It contained two forms of sizes 1200 and 1050 bp distinct at the 5' UTR. The coding… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
7
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 51 publications
(81 reference statements)
1
7
0
Order By: Relevance
“…In P. monodon , silencing of early endosome antigen 1 (EEA1) protein ( Pm EEA1), involving in early endosome fusion, caused a delay in shrimp mortality due to YHV infection 35 . Similar results were observed in YHV-challenged shrimp with either Pm Rab7 or Pm Rab11 suppression 6 , 36 . These suggested that endosome trafficking plays an important role during YHV infection.…”
Section: Discussionsupporting
confidence: 84%
“…In P. monodon , silencing of early endosome antigen 1 (EEA1) protein ( Pm EEA1), involving in early endosome fusion, caused a delay in shrimp mortality due to YHV infection 35 . Similar results were observed in YHV-challenged shrimp with either Pm Rab7 or Pm Rab11 suppression 6 , 36 . These suggested that endosome trafficking plays an important role during YHV infection.…”
Section: Discussionsupporting
confidence: 84%
“…Similar results were reported in PmRab11 and PmRab7. Silencing PmRab11 10 , PmRab7 52 , 53 or LvRab7 54 resulted in inhibition of viral replication in shrimp. For instance, the co-localization between PmRab11 and YHV was observed in hemocytes at 24 to 72 h post viral injection, whereas in PmRab11 knockdown hemocytes, a low level of co-localization of PmRab11 and YHV was detected at the perinuclear region at 24–72 h. These results revealed that PmRab11 is required for YHV infection in shrimp cells 10 .…”
Section: Discussionmentioning
confidence: 99%
“…Silencing PmRab11 10 , PmRab7 52 , 53 or LvRab7 54 resulted in inhibition of viral replication in shrimp. For instance, the co-localization between PmRab11 and YHV was observed in hemocytes at 24 to 72 h post viral injection, whereas in PmRab11 knockdown hemocytes, a low level of co-localization of PmRab11 and YHV was detected at the perinuclear region at 24–72 h. These results revealed that PmRab11 is required for YHV infection in shrimp cells 10 . In addition, silencing of PmRab7 resulted in significant inhibition of WSSV-VP28 mRNA and YHV replication, suggesting that PmRab7 required for WSSV and YHV infection in shrimp cell 52 .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations